Cobalt mixed oxides deposited on the SiC open-cell foams for nitrous oxide decomposition - Klegova, A.; Inayat, A.; Indyka, P.; Gryboś, J.; Sojka, Z.; Pacultová, K.; Schwieger, Wilhelm; Volodarskaja, A.; Kuśtrowski, P.; Rokicińska, A.; Fridrichová, D.; Obalová, L. (Applied Catalysis B-Environmental, 2019)
Supported Co3O4 and Co4MnAlOx mixed oxides were prepared by deposition on the SiC open-cell foams by wet impregnation and suspension methods and characterized by AAS, BET, XRD, SEM, TEM, TPR-H2, XPS and nitrogen adsorption methods. Prepared supported catalysts as well as active phase Co3O4 and Co4MnAlOx in grain form prepared from parent solutions were tested for nitrous oxide decomposition. Catalytic activity of grain active phase was governed by methods of preparation; Co3O4 and Co4MnAlOx prepared by suspension method were significantly more active than those from solutions for impregnation method. Suspension method provided active phase with higher surface areas and sites with better reducibility, both of these factors contributed to higher N2O conversions. In contrast to this, N2O conversions over supported catalysts were dependent more on chemical composition of active phase than on method of preparation. Both catalysts containing Co4MnAlOx mixed oxide revealed higher conversion of N2O than catalysts containing Co3O4. STEM analysis of the most active Co4MnAlOx prepared by suspension method showed (i) segregation of Co3O4 nanocrystals of cuboctahedral shape containing (100) and (111) facets (this segregation was confirmed also by XPS and TPR-H2) and (ii) Co-Mn-Al oxide nanoparticles with very small un-faceted grains assembled into elongated fiber-like agglomerates were observed by STEM.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Cobalt mixed oxide; N; Open-cell foam; SiC; Supported catalyst